Analisis Kinerja Struktur pada Bangunan Bertingkat dengan Metode Analisis Respon Spektrum Berdasarkan SNI 1726:2019: Analysis of Structure Performance in Multistory Buildings with Response Spectrum Analysis Method Based on SNI 1726:2019 - Muhammad Hilmi; Erizal; Joana Febrita (Departemen Teknik Sipil dan Lingkungan, IPB University, 2021)
The issuance of SNI 1726:2019 indicates that the planning has passed a certain transition period so that the existing regulations will no longer apply. The planning that has been made for the Collaborative Research Center (CRC) buildings still uses the standards that were previously in place. This study aims to analyze the performance of structures in CRC buildings with spectrum response analysis methods based on SNI 1726:2019. The research method is carried out in several stages, starting from data collection, structure modeling, loading analysis, structure conformity analysis, and structure performance check. Modeling of CRC building structures is done based on the image of as built drawing contractors. Calculation of loading on building structures includes gravitational and lateral loads. The amount of mass participation obtained has been more than 90%, while the value of the period of structure and dynamic basic shear force has been controlled so that it meets the requirements in accordance with SNI 1726:2019. Based on the drift ratio value, the performance level of the CRC buildings is Immediate Occupancy (IO). The result of checking the influence of P-Delta obtained θ value does not exceed θmaks so that it can be categorized as safe.